Pengaruh Pendidikan Kesehatan tentang Mencuci Tangan pada Masa Pandemi Covid-19 - Sidabutar, Sondang; Sumantrie, Pipin (Window of Health : Jurnal Kesehatan, 2021)
COVID-19 is a contagious disease caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), which is thought to spread among people through respiratory droplets produced when coughing and splashes from someone who is sneezing and acquired from the surface of objects. contamination and then accidentally touches someone's face. One of the groups most vulnerable to being infected with COVID-19 is the elderly, the Pematangsiantar Elderly Social Service is a place for the elderly to live without depending on their children or their families. This is an age group that is very vulnerable to the transmission of COVID-19, so it is necessary for them to be able to understand how to prevent COVID-19. One way to prevent COVID-19 is to wash your hands. Washing hands is an inexpensive and easy routine, an important part of infection control procedures, and is the best method for preventing the transmission of microorganisms. The purpose of this study was to analyze the effect of health education on hand washing during the COVID-19 pandemic at the Pematangsiantar Elderly Social Service. The design of this research is a One-Group Pretest-Posttest Design study. This is a form of Pre-Experimental Design. The population and sample in this study were 30 elderly people. The pre-test results got an average value of 2.37 while the post-test results got an average value of 9.67. Based on the SPSS test that has been carried out (P = 0.000; Î± = 0.05) Ha (alternative hypothesis) is accepted because the p-value is â‰¤ 0.005, so that Ho is rejected at a price of level of significance (Î±) = 5% so that the alternative hypothesis is accepted. Thus the conclusion in this study is that there is a difference in knowledge before and after being given health education about washing hands during the COVID-19 pandemic at the Pematangsiantar Elderly Social Service. Keywords: COVID-19; Elderly; Washing hands.